(untitled) (Czech Journal of International Relations, 2008)
Non-governmental organizations participate more than two decades on post-conflict reconstruction and peace-building. They participated on reconstruction of Bosnia and Herzegovina, Angola and Haiti. Existing experiences with post-conflict reconstruction shows that NGOs play a positive roles in the process. On the basis of analysis of post-conflict reconstruction in various countries the author thinks that the positive relationship between NGOs and governments by the post-conflict reconstruction and peace-building is weakening. Why after more than decade of successful evolution of relationship between NGOs and governments in the process of post-conflict reconstruction the skepticism about this relationship emerges? On the case study of post-conflict reconstruction of Afghanistan the possible answer will be offered.